The variable clinical course of peripartum cardiomyopathy - Krejci, Jan; Hude, Petr; Spinarova, Lenka; Zampachova, Vita; Sirotkova, Alzbeta; Freiberger, Tomas; Nemcova, Eva; Vitovec, Jiri (Biomedical papers, 2014)
Background: In Europe, peripartum cardiomyopathy (PPCM) is a rare disorder, often difficult to diagnose and it has a variable clinical course. The aim of this report was to describe and discuss the individual variability of this disorder and its management.Patients and Methods: Three cases of PPCM manifesting as severe heart failure are compared. Common was the presence of myocardial inflammation detected by endomyocardial biopsy. Different were treatment methods and clinical course. Modern therapeutic concepts such as immunosuppressive therapy and bromocriptin administration are discussed, as well as non-pharmacological approaches.Conclusion: In the differential diagnostics of dyspnea associated with pregnancy and childbirth, PPCM should be considered. The potentially severe course of the disease requires hospitalization with the possibility of comprehensive heart failure treatment, including non-pharmacological approaches such as device therapy and heart transplantation.
Keywords: peripartum cardiomyopathy; myocarditis; echocardiography; endomyocardial biopsy; therapy